IMPLEMENTATION STUDY IN PREVENTION AND CONTROL OF DRUG-RESISTANT TUBERCULOSIS DURING THE COVID-19 PANDEMIC IN DUSHANBE - Z.KH. TILLOEVA (Avicenna Tajik State Medical University, 2022)
Objective: To assess an implementation study (IS) aimed at improving the epidemiological surveillance of tuberculosis (TB) and drug-resistant TB (DRTB) in Dushanbe during the COVID-19 pandemic. Methods: IS assessment was carried out according to the RE-AIM framework and WHO recommendations for reporting on IS. To assess the effectiveness of the action taken, official statistics and reports from the City Center for Protection of Population from Tuberculosis were used. Results: IS was a qualitative study. The study was supported by the WHO Special Program for Research and Training in Tropical Diseases (TDR). A multidisciplinary team led by the Dushanbe City Health Department has undertaken the following measures: introduction of a system of weekly epidemiological surveillance for TB at the primary health care (PHC) level from the second week of 2021; involvement of students of basic and advanced field epidemiology programs (FETP) in the assessment of the TB epidemiological surveillance system; tracking of registered patients with laboratory confirmation of TB; application of data from the quarterly reports in tracking the diagnostic trends and evaluation of the effectiveness of DR-TB treatment. All materials received were documented and used to train TB doctors and PHC workers. Only 66% of TB doctors were involved in capacity building in Dushanbe PHC: 24.4% of PHC workers were trained in the basics of TB diagnosis and treatment. Stabilization of TB and DR-TB rate was achieved in 2021 compared to 2020 (morbidity growth rates were 2.7% and 11.9%, respectively); effectiveness of treatment of TB with preserved sensitivity of M. tuberculosis (MBT) to anti-TB drugs in the 2020 cohort increased, but efficacy of DR-TB treatment in the 2019 cohort decreased. Conclusion: IS has identified major barriers to achieving the TB elimination goals. Although the data indicate stabilization of TB and DR-TB incidence rates and increased effectiveness of drug-sensitive TB treatment in Dushanbe, further monitoring and achievement of sustainable results are required.